Potential of Exserohiulm monoceras as bioherbicide for controlling Echinocloa crus-galli (Rumput Sambau). - Sajili, Mohammad Hailmi; Kadir, Jugah; Abdullah, Tajul Afif; Suhili, Zarizal; Mohamad, Noor Muzamil; B., Mohd Nazri; N., Norhayati; B., Noor Afiza; M., Salmah (Universiti Sultan Zainal Abidin, 2011)
The fungus isolated from diseased Echinochloa crus-galli was identified as Exserohilum monoceras, based on the conidial morphology, germination characteristics and hilum morphology. The objectives of this study were to screen and isolate fungal pathogen of E. monoceras from infected E. crus-galli as well as to determine the pathogenicity of E. monoceras and the optimum conditions for growth and sporulation of E. monoceras. In repeated trials, the pathogenicity of this fungus to its host was confirmed by Koch’s postulate. The pathogen caused a high level of disease on E. crus-galli where symptoms appeared within 24 h of inoculation. It induced eyespot lesions typical of infection by Exserohilum spp. and induced a severe ‘burnt’ appearance on the foliage of E. crus-galli. The leaf tissues in the vicinity of heavy infestation were completely killed. The disease did not develop on non-inoculated plants, which was indicative of localized infection and lack of significant secondary disease cycles. The laboratory study indicated that better growth and appressoria production can be attained when the fungus is exposed to temperature in the range of 25 to 30 oC. This study also indicated that Maxigreen®, which is an adjuvant, when mixed with sunflower in the ratio of 0:5:7 is ideal for formulating the conidia. This research has illustrated that solid media such as agar is an excellent growth media, but spore production has been influenced by the nutrient content of the media. The best medium for sporulation was half strength V8 juice agar.